Muslim American Activism in the Age of Trump. (3rd April 2018) - Yukich, Grace
Abstract: The presidency of Donald Trump has roused progressive Americans, including religious progressives, to become more involved in politics. While Muslim Americans are not uniformly progressive, many have serious concerns about Trump's presidency, partly rooted in his anti-Muslim rhetoric and policies. This article asks: how are Muslim Americans responding to the Trump era, and what can this teach us about religious activism in the United States today? Using key websites, social media, and newspaper sources, I identify eight ways Muslims are reacting to the Trump presidency. This article demonstrates the diversity of Muslim American activism and challenges the assumption that all Muslims are opposed to Trump. It also shows how common conservative/progressive categorizations are often inadequate for understanding the activism of religio-racial minorities. In doing so, this article both sketches a picture of Muslim American activism in this era and creates an agenda for research on Muslim American activism in the coming years.